Loci on 20q13 and 21q22 are associated with pediatric-onset inflammatory bowel disease - Kugathasan, Subra; Baldassano, Robert N; Bradfield, Jonathan P; Sleiman, Patrick M A; Imielinski, Marcin; Guthery, Stephen L; Cucchiara, Salvatore; Kim, Cecilia E; Frackelton, Edward C; Annaiah, Kiran; Glessner, Joseph T; Santa, Erin; et al. (Nature genetics, 2008)
Hakon Hakonarson and colleagues report the identification of two new susceptibility loci for inflammatory bowel disease (IBD). One variant is near a gene encoding tumor necrosis factor receptor subfamily member 6B and is associated with increased levels of this protein in serum from individuals with IBD. Inflammatory bowel disease (IBD) is a common inflammatory disorder with complex etiology that involves both genetic and environmental triggers, including but not limited to defects in bacterial clearance, defective mucosal barrier and persistent dysregulation of the immune response to commensal intestinal bacteria. IBD is characterized by two distinct phenotypes: Crohn's disease (CD) and ulcerative colitis (UC). Previously reported GWA studies have identified genetic variation accounting for a small portion of the overall genetic susceptibility to CD and an even smaller contribution to UC pathogenesis. We hypothesized that stratification of IBD by age of onset might identify additional genes associated with IBD. To that end, we carried out a GWA analysis in a cohort of 1,011 individuals with pediatric-onset IBD and 4,250 matched controls. We identified and replicated significantly associated, previously unreported loci on chromosomes 20q13 (rs2315008[T] and rs4809330[A]; P = 6.30 × 10 −8 and 6.95 × 10 −8 , respectively; odds ratio (OR) = 0.74 for both) and 21q22 (rs2836878[A]; P = 6.01 × 10 −8 ; OR = 0.73), located close to the TNFRSF6B and PSMG1 genes, respectively.